Литература русского зарубежья. 1920-1940 - Михайлов О. Н. (2000)
Экземпляры: ЧЗ (20151218) / Инвентарный номер: 35617 / Цена: 34.00 / Сис.шифр: 83.3(2Рос=Рус) / Авт.знак: Л 64 / ГРНТИ: 17 / ББК: 83.3(2Рос=Рус)